(untitled) (Research, Society and Development, 2022)
The objective of the study is to report the case of a female patient with double sorological confirmation in rapid tests for anti-HIV antibodies for more 10 years, being follow up by the Service Specialized Attendance/Testing and Counseling Center, who never showed signs of clinical disease progression and maintain an undetectable viral load even in the absence of any antirretroviral therapy. A case of great relevance for the scientific community, given the rarity of the clinical evolution presented and the morbidity and mortality of this type of infection in Brazil, since according to data from the Ministry of Health the number of infected is close to 1 million. The possibility of natural control of human immunodediciency virus (HIV) infection without antiretroviral therapy, such as the one reported in the case, opens perspectives for understanding the specific immunological and biomolecular mechanisms involved in protection and for the possibility of a spontaneous functional cure of the infection.